Exploring The Horizontal Static and Dynamic Shading Devices to Minimize Cooling Load in Tropical Buildings - Fitriatulamal, Hilmi; Dewi, Ova Candra; Alkadri, Miktha Farid; Rahmasari, Kartika (UI Scholars Hub, 2025)
Shading devices are essential for reducing solar radiation and cooling loads in buildings located in tropical climates. In the Jakarta region, the highest solar factor is observed on west- and east-facing facades, followed by north- and south-facing orientations. National building policy in Indonesia encourages facades to face north–south to reduce solar heat gain. This study explores horizontal static and dynamic shading devices on north-facing facades and evaluates their impact on cooling load reduction and daylight performance. The methodology includes calculating and simulating energy use intensity (EUI) using EnergyPlus and conducting illuminance analysis using Radiance and Grasshopper. Key parameters considered in the shading design include sun position, illuminance levels, and EUI. The results show that static shading devices with a fixed tilt angle of 20° and a depth of 1.2 m reduce the cooling load by 15.82% while ensuring that at least 30% of the workspace floor area receives an average illuminance of 300 lux throughout the year. Meanwhile, dynamic shading devices with adjustable tilt angles ranging from 10° to 40°, following the sun’s position, reduce the cooling load by 15.75%–18.83%. This configuration consistently ensures that at least 30% of the workspace floor area achieves 300 lux of illuminance each month. These findings provide a practical reference for the design of north-facing shading devices in tropical climates, balancing thermal performance and daylight availability.